Técnicas de caracterização para investigar interações no nível molecular em filmes de Langmuir e Langmuir-Blodgett (LB) - Ferreira, Marystela [UNESP]; Caetano, Wilker [UNESP]; Itri, Rosangela; Tabak, Marcel; Oliveira Jr., Osvaldo N. (Sociedade Brasileira de Química, 2005)
This paper discusses fundamental concepts for the characterization of Langmuir monolayers and Langmuir-Blodgett (LB) films, with emphasis on investigations of material properties at the molecular level. By way of illustration, results for phospholipid monolayers interacting with the drug dipyridamole are highlighted. These results were obtained with several techniques, including in situ grazing incidence X-ray diffraction, Fourier transform infrared (FTIR) spectroscopy, fluorescence microscopy, in addition to surface pressure and surface potential isotherms. Also mentioned are the difficulties in producing Langmuir and LB films from macromolecules, and how molecular-level interactions in mixed polymer LB films can be exploited in sensors.
Characterization techniques to investigate molecular-level interactions in Langmuir and Langmuir-Blodgett (LB) films
Keywords: Langmuir and Langmuir-Blodgett (LB) films; characterization; interface